MENGURAI BENANG KUSUT PROBLEMATIKA SUPERVISI: UPAYA KONSEPTUAL PENJAMINAN MUTU PENDIDIKAN - Putri Norsafitri; Perdaus; Oktavia Nur Safitri; Bidin (AL-IBNOR, 2026)
Educational supervision plays a strategic role in ensuring and improving the quality of education. However, its implementation still faces various challenges, including the dominance of administrative orientation, limited supervisory competence, negative perceptions among teachers, weak follow-up mechanisms, and the demands of digital transformation. These issues indicate a discrepancy between the ideal concept of supervision and its practical implementation. This study employed a qualitative approach with a library research design to analyze various scholarly sources related to educational supervision and quality assurance. Data were collected through documentation and literature review and analyzed using content analysis techniques. The findings reveal that strengthening educational supervision requires a paradigm shift from a controlling approach to a collaborative and humanistic one. In addition, improving supervisors’ competencies, optimizing follow-up actions, and integrating digital technology are essential strategies to enhance the effectiveness of supervision as an instrument of educational quality assurance. Therefore, educational supervision should be positioned not merely as an administrative activity but as a continuous professional development mechanism aimed at fostering a sustainable quality culture in educational institutions.